2019
DOI: 10.1016/j.solmat.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adhesion forces between dust particles and photovoltaic module surfaces

Abstract: Soiling of Photovoltaic (PV) modules is a growing area of concern due to the adverse effect of dust accumulation on PV performance and reliability. In this work, we report on four fundamental adhesion forces that take place at the first stage of soiling process. These are capillary, van der Waal, electrostatic and gravitational forces. It is found that under high relative humidity, the adhesion mechanism between dust particles and PV module surfaces is dominated by capillary force, while van der Waal force dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…High humidity causes water (including soluble particles) to condense between the insoluble particles and the surface. Capillary adhesion forces are most dominant at high humidity [25], which are caused by surface tension at the liquid-solid interface and the Laplace pressure (pressure between the atmosphere and liquid meniscus) [24]. When the liquid evaporates, particles compact together due to surface tension.…”
Section: Cementationmentioning
confidence: 99%
“…High humidity causes water (including soluble particles) to condense between the insoluble particles and the surface. Capillary adhesion forces are most dominant at high humidity [25], which are caused by surface tension at the liquid-solid interface and the Laplace pressure (pressure between the atmosphere and liquid meniscus) [24]. When the liquid evaporates, particles compact together due to surface tension.…”
Section: Cementationmentioning
confidence: 99%
“…However, Valerino et al (Valerino et al, 2020) reported that, even if large particles are dominant in terms of deposited mass, the soiling losses are mainly caused by the small particles. Nonetheless, Isaifan et al (Isaifan et al, 2019) showed that only a fraction of the suspended PM 10 deposits on the PV module surface and the so-called PM 10 sticky-fraction is correlated to the relative humidity through a modified sigmoid function with an inflection point at 70% RH. Above this value most of the PM is deposited, due to the action of capillary forces.…”
Section: Estimation Of Soiling From Environmental Parametersmentioning
confidence: 99%
“…Field tests showed that the dust accumulation lowers for surfaces facing toward the wind, compared with facing downwind at the same tilt angle. Isaifan et al., 2019 2019 Doha, Qatar Tropical and subtropical desert climate PM, relative humidity Showed that the fraction of the PM 10 depositing on a PV panel surface changes depending on the relative humidity. The correlation between PM and the performance ratio have an R 2 = 0.94 when using only the sticky-fraction of the airborne particulate matter concentration.…”
Section: Estimation Of Soiling From Environmental Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The forces mainly include adhesion forces and detachment forces (surface tension force and hydrodynamic force). For small dust particles (diameter < 500 µm), the adhesion forces are mainly van der Waals forces and the electrostatic force in dry environments, as well as the capillary force in humid environments 3,37 . The adhesion force for a single particle on a surface can be in the range of 100~300 nN, as characterized by an AFM tip 3 .…”
Section: Dust Particle Adhesion Force and Water Droplet Cleaning Forcementioning
confidence: 99%